Unwinding the Long Road that leads to Understanding Autoimmunity - Florencia Rosetti; José C. Crispín (Permanyer, 2021)
Systemic autoimmune diseases are complex clinical conditions that arise in genetically predisposed individuals as a result of the interplay between their immune system and their environment. In this perspective, we briefly discuss our current understanding of the pathogenesis of autoimmunity and indicate four research avenues whose exploration will bring us closer to resolving fundamental questions that remain unanswered in this enigmatic field.